Temperature and humidity in the Brazilian tropical summer affecting the in vivo embryo production of Nelore breed in superovulation program - Macedo, Gustavo Guerino; Zúccari, Carmem Estefânia; Costa e Silva, Eliane Vianna (Archives of Veterinary Science, 2012)
This study used Nelore embryo donors to evaluate the effects of summer temperatures and humidity in a tropical area on embryo recovery. Seventeen cows were randomly assigned to three groups (G1, G2 and G3) as well as 28 heifers into four groups (G4, G5, G6 and G7), and underwent a consecutive 4 d superovulation protocol (Day 0 to 3) and two artificial inseminations (AI; Day 4 and 5). Cortisol concentrations were determined on Day 0, 4 and 5. Temperature and humidity index (THI) was recorded from Days 0 to 7. Embryos were recovered on Day 11, and evaluated for quality and quantity. Heifers experienced higher thermal load than cows, however, there was no difference in the cortisol and reproductive parameters measured between both. The THI measured throughout the experiment oscillated between 65.8 and 85.2 (76.1 ± 3.9), which is a dangerous range for thermal comfort, especially above 78. Animals from G5 were subjected to high THI throughout the experimental protocol, approaching a dangerous condition (78.7 ± 0.9) on Day 4 (first AI). The THI for G2 cattle was also high, as in the other groups, but increased to over 80 two days after AI. Animals from group G5 had the lowest viable production being 2.4 ± 0.9 embryos (38% of viability), followed by cattle from group G2 (3.0 ± 0.9 viable, P<0.05). Thus, high thermal load in the summer expressed by high THI, on the day and post- insemination days (during embryo cleavage), compromises embryo numbers, viability and consequently reproductive performance of Nelore females.